The lacemaker [large type] - Frantz, Laura (Thorndike Press, a part of Gale, a Cengage Company, 2018)
Lady Elizabeth "Liberty" Lawson, daughter of the British lieutenant governor of the Virginia Colony, seems to have her life in order. But colonial Williamsburg is a powder keg on the verge of exploding, and her fiance's cousin Noble Rynallt carries the flame of revolution in his heart. Will she stay true to her English roots, or side with Noble and the radical revolutionaries?